Translating Implicit Meaning of English Texts into Indonesian - Zulprianto Zulprianto (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
Translation can help the language learners/translators realize the possibility of conveying the message of source text (ST) in many different ways in the target text (TT). A text, which is a product of language, is a unit whose parts contain information, explicit or implicit, connected in various ways with the aid of cohesive devices. At the one end, the cohesive devices help tie the parts of the texts, but at the other end, they may result in producing implicit meaning. If the explicit information is indicated by the presence of lexical items and grammatical forms, the implicit one is formless or at least modestly marked. Among the cohesive devices responsible for making the implicit meanings are the use of reference, substitution, and ellipsis. In case of translation, if a text containing the cohesive devices is to be translated, the translator has options to shift or keep the level of their explicitness. This article attempts to examine how these cohesive markers are translated by analyzing some Indonesian translations of different short stories by Oscar Wilde. The analysis demonstrates the translators tend to keep the implicit meaning of the source language (SL) in the target language (TL). This may owe to two explanations: the translators are not aware of the implicit information in the SL and are tempted to employ literal translation. However, the explanation by no means discredits the translators as they may deliberately translate so and their translations are possible in the structure of the TL